Peran Modal dan Biaya Produksi dalam Meningkatkan Pendapatan UMKM di Kediri, Jawa Timur - Dida Maulidya Al Afshana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of capital variables and production costs on the income of Micro, Small, and Medium Enterprises (MSMEs) in the Kediri area, East Java. The method used is a descriptive quantitative approach with data collection techniques through the distribution of questionnaires to MSME actors. Data analysis was performed using multiple linear regression with the help of SPSS software version 26. The results of the study show that both capital and production costs have a significant influence on the income of MSMEs. Capital plays a key role in supporting business operations and expansion, while production costs affect efficiency and profit margins. These findings indicate that increasing access to capital and optimal management of production costs can be an important strategy in increasing MSME income. This research provides practical contributions for stakeholders, including local governments and financial institutions, in designing policies for empowering MSMEs that are more targeted. In addition, the results of this study can be a reference for further research that focuses on other variables that also affect the performance of MSMEs. Thus, a deeper understanding of microeconomic factors can encourage the sustainable growth of the MSME sector in the Kediri area and its surroundings.